(untitled) (ACTA MEDICA PERUANA, 2022)
Objective: To determine the barriers in the management of health facilities that serve the indigenous and Afro-descendant population in Peru. Material and methods: A virtual survey on health management was designed for first level health care personnel in 89 health facilities (EESS) in 27 provinces during October and November 2021. Results: In 73% of the EESS, the personnel reported not knowing the plan against the third pandemic wave, 14.8% of the EESS reported not being trained in the management of COVID-19, in 22.7% of the EESS they met to coordinate how to face the third pandemic wave, in 83% of the EESS the personnel reported not having a budget for their plan against COVID-19. Conclusions: There are barriers in the vision, management and budget in EESS that serve indigenous and Afro-Peruvian populations, which would affect the effective execution of strategies for the control of the pandemic by COVID-19.